The Role of Career Woman in Islamic Education Field in a Digital Era - Anisa Dwi Makrufi (International Islamic Schools Alliance, 2016)
This paper aims to analyses the role of career woman in Islam especially Islamic education in a digital, modern era. To this end, analyses on the relevant literature have been carried out. As a result, an educated family with values of Islam is the greatest favors. In a family, a woman has a central role in Islamic education. Nowadays, many women opt for a career outside their home. In Islam it is allowed, even in the recorded history, several women who became wives of the Prophet also became career women. Islam provides a strong motivation for women to run their careers in any fields in accordance with their nature and dignity without leaving their duties as ra’iyah fi baiti zaujiha (person(s) in charge of the internal problems of households). The role of a career woman in the field of Islamic education is a challenge. Considering the fact of the digital era, it is significantly important to take account of the concept of monotheism. It is the single concept referring to that of God, the Absolute Power. In this digital era, the principle of tauhid as the main one of monotheism itself is to stand for a belief that Allah, the only God, encompasses all the things. In short words, the digital age would bring people into the circumtance where they are united to be faithful to God Almighty. In the sense, career women are eble to optimize their roles in lifting this tauhid value as well as especially educating their family.